2016
DOI: 10.1200/jco.2015.63.0152
|View full text |Cite
|
Sign up to set email alerts
|

Medical Education and Training: Building In-Country Capacity at All Levels

Abstract: Poorly trained workers and limited workforce capacity contribute immensely to barriers in cancer control in low- and middle-income countries (LMICs). Because of an increasing disease burden and the gap in trained personnel, it is critical that LMICs must develop appropriate in-country training programs at all levels to adequately address their cancer-related outcomes. The training in LMICs of cancer health personnel should address priority cancer diseases in the specific country by developing caregivers, train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…For instance, out of every seven women in Kenya, six have not been screened for breast cancer [ 15 , 16 ]. The disease strikes 1 in 9 women due to late diagnosis according to the Kenya National Cancer Control strategy and as observed on burden of breast cancer and contributing factors of high mortality [ 23 , 39 41 ]. Most women hardly seek professional medical attention untill symptomatic pointers are advanced [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, out of every seven women in Kenya, six have not been screened for breast cancer [ 15 , 16 ]. The disease strikes 1 in 9 women due to late diagnosis according to the Kenya National Cancer Control strategy and as observed on burden of breast cancer and contributing factors of high mortality [ 23 , 39 41 ]. Most women hardly seek professional medical attention untill symptomatic pointers are advanced [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In observing the disparate burden of illnesses on communities in LMICs, Buser et al and several other investigators found an unmet need for training and education to handle diseases and interventions in these communities 4–7. Recently, initiatives sponsored by the Robert Wood Johnson Foundation, the Institute for Healthcare Improvement, the Bill & Melinda Gates Foundation, and the Global Fund to Fight AIDS, Tuberculosis and Malaria have focused on improving the work environment to attract nursing staff and to provide continuing education to healthcare workers 8 9.…”
Section: Introductionmentioning
confidence: 99%
“…Leadership was identified as a key attribute of successful consortium management in over a third of papers. It was deemed a major determinant of consortium success or failure,49 83 and its pivotal role was also demonstrated when some consortia faced leadership changes 43 60 77. As noted by an author,…”
Section: Resultsmentioning
confidence: 99%
“…Linkages made included observations that programme designs focusing on a wide range of human and infrastructural capacities25 85 86 across micro-, meso- and macro-levels49 73 77 87 produce more synergistic interactions and sustainable capacity. Acknowledging existing capacities of all partners and according mutual respect were noted to promote multidirectional capacity transfer,29 49 81 88 and correspondingly tailoring partners’ participation resulted in more contextually relevant and sustainable outcomes 42 76 82 83. The significance of consortium management in achieving research capacity strengthening outcomes is increasingly being acknowledged 25 59 73.…”
Section: Resultsmentioning
confidence: 99%